2001
DOI: 10.1103/physrevb.64.241104
|View full text |Cite
|
Sign up to set email alerts
|

Large thermoelectric power factor inTiS2crystal with nearly stoichiometric composition

Abstract: A TiS 2 crystal with a layered structure was found to have a large thermoelectric power factor. The in-plane power factor S 2 /ρ at 300 K is 37.1 µW/K 2 cm with resistivity (ρ) of 1.7 mΩcm and thermopower (S) of -251 µV/K, and this value is comparable to that of the best thermoelectric material, Bi 2 Te 3 alloy.The electrical resistivity shows both metallic and highly anisotropic behaviors, suggesting that the electronic structure of this TiS 2 crystal has a quasi-twodimensional nature. The large thermoelectri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
115
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(127 citation statements)
references
References 25 publications
(37 reference statements)
11
115
1
Order By: Relevance
“…Therefore, we proposed the idea of a 'natural superlattice' produced by intercalating a layer of SnS into the van der Waals gap of layered TiS 2 [29,30]. The TiS 2 layer can provide thermopower as well as the electron pathway according to Imai's research on TiS 2 single crystals [31]. The intercalated SnS layer can suppress the transport of phonons as a consequence of the interaction between the SnS layer and TiS 2 layer and/or disruption of the periodicity [18], CsBi 4 Te 6 [14], Tl 9 BiTe 6 [9], silicon nanowires [21], LaFe 3 CoSb 12 [12] and ErAs embedded in the InGaAlAs matrix [34].…”
Section: The Concept Of 'Natural Superlattice'mentioning
confidence: 99%
“…Therefore, we proposed the idea of a 'natural superlattice' produced by intercalating a layer of SnS into the van der Waals gap of layered TiS 2 [29,30]. The TiS 2 layer can provide thermopower as well as the electron pathway according to Imai's research on TiS 2 single crystals [31]. The intercalated SnS layer can suppress the transport of phonons as a consequence of the interaction between the SnS layer and TiS 2 layer and/or disruption of the periodicity [18], CsBi 4 Te 6 [14], Tl 9 BiTe 6 [9], silicon nanowires [21], LaFe 3 CoSb 12 [12] and ErAs embedded in the InGaAlAs matrix [34].…”
Section: The Concept Of 'Natural Superlattice'mentioning
confidence: 99%
“…Previous experimental studies [12] have reported that nearly stoichiometric TiS 2 shows a large power factor value of 37.1 µW/K 2 -cm at room temperature that is comparable with the best thermoelectric material Bi 2 Te 3 [13]. The large power factor originates from a sharp increase in the density of states just above the Fermi energy as well as the inter-valley scattering of charge carriers [12,14,15]. However, the semimetallic nature of TiS 2 gives rise to bipolar effects which are not desirable for thermoelectric applications [16].…”
mentioning
confidence: 99%
“…Layered TiS 2 (titanium disulfide), one type of thermoelectric materials, has been reported to show a high power factor at room temperature but shows a low thermoelectric figure of merit, ZT (=S 2 ·T/¬, where S is Seebeck coefficient, · electrical conductivity, T the absolute temperature, and ¬ thermal conductivity), because of its high thermal conductivity. 1) Various efforts have been reported to reduce its thermal conductivity and one successful approach is forming a (SnS) 1.2 (TiS 2 ) 2 natural superlattice by intercalating an SnS layer into the TiS 2 Van der Waals gaps. The thermal conductivity was found to be reduced due to the softening of the transverse phonon velocity because of weakening of interlayer bonding by the intercalated SnS layer and a ZT value of 0.37 at 700 K was attained.…”
Section: Introductionmentioning
confidence: 99%